Wearable biosensors to monitor workload in dancers: A systematic review - Wiese, K. R.; Ambegaonkar, J. P.; Martin, J.; Kenny, S. J.; Hansen-Honeycutt, J.; Pisay, P.; Miller, A. (Journal of Dance Medicine & Science, 2026)
Introduction: Dancers are aesthetic athletes with high workloads similar to sport athletes. Wearable biosensors are used in athletics to assess workload and inform training decisions to optimize performance and reduce fatigue and injury risk. While workload monitoring methods in dancers have been systematically reviewed, limited research specifically examines using wearable biosensors for this purpose. Thus, this study aims to systematically review how wearable biosensors are used to monitor workload in dancers.